Connexin 43, breast cancer tumor suppressor: Missed connections?. Issue 1 (28th April 2016) - Grek, Christina L.; Rhett, J. Matthew; Bruce, Jaclynn S.; Ghatnekar, Gautam S.; Yeh, Elizabeth S.
Highlights: Connexin 43 is a conditional tumor suppressor protein in breast cancer. Altered Connexin 43 expression and/or localization are potential biomarkers in primary breast cancers. Loss of function of Connexin 43 in gap junctions is a potential mechanism for breast cancer metastasis. Restoring Connexin 43 gap junction intercellular communication may treat breast cancer progression and metastasis. Abstract: Connexins are a family of transmembrane proteins that are characterized by their capacity to form intercellular channels called gap junctions that directly link the cytoplasm of adjacent cells. The formation of gap junctions by connexin proteins facilitates intercellular communication between neighboring cells by allowing for the transfer of ions and small signaling molecules. Communication through gap junctions is key to cellular equilibrium, where connexins, and the gap junction intercellular communication that connexins propagate, have roles in cellular processes such as cell growth, differentiation, and tissue homeostasis. Due to their importance in maintaining cellular functions, the disruption of connexin expression and function underlies the etiology and progression of numerous pathologies, including cancer. Over the past half a century, the role of connexins and gap junction intercellular communication have been highlighted as critical areas of research in cellular malignancies, and much research effort has been geared toward understanding their dysfunction in human cancers. Although ample evidence supports the role of connexins in a variety of human cancers, detailed examination in specific cancers, such as breast cancer, is still lacking. This review highlights the most abundant gap junction connexin isoform in higher vertebrate organisms, Connexin 43, and its role in breast cancer.